Peran Layanan Bimbingan dan Konseling terhadap Penanganan Masalah Belajar Siswa - Raihanah Amni; Husrin Konadi; Riska Rahmadewi (Malewa: Journal of Multidisciplinary Educational Research, 2026)
This study aims to analyze the role of guidance and counseling (GC) services in overcoming students' learning difficulties. This research employs a qualitative approach with a case study method. The research subjects include guidance and counseling teachers, students experiencing learning difficulties, and parents. Data collection techniques consist of interviews, observations, and document analysis, while data analysis uses thematic analysis. The results indicate that students' learning problems include low learning motivation, difficulty in understanding learning materials, lack of concentration, and academic anxiety. Guidance and counseling services such as individual counseling, group guidance, and information services play an important role in addressing these problems. Individual counseling is considered the most effective service as it allows students to express their problems in depth. The effectiveness of GC services is influenced by the competence of counselors, students’ openness, and support from parents and the school environment. The findings indicate that guidance and counseling services have a strategic role in improving students’ learning abilities optimally.